Functional Characterization of Rare Genetic Variants in the N-Terminus of Complement Factor H in aHUS, C3G, and AMD - Wong, Edwin K. S.; Hallam, Thomas M.; Brocklebank, Vicky; Walsh, Patrick R.; Smith-Jackson, Kate; Shuttleworth, Victoria G.; Cox, Thomas E.; Anderson, Holly E.; Barlow, Paul Nigel; Marchbank, Kevin James; Harris, Claire L.; Kavanagh, David (Frontiers in immunology, 2021)
Membranoproliferative glomerulonephritis (MPGN), C3 glomerulopathy (C3G), atypical haemolytic uraemic syndrome (aHUS) and age-related macular degeneration (AMD) have all been strongly linked with dysfunction of the alternative pathway (AP) of complement. A significant proportion of individuals with MPGN, C3G, aHUS and AMD carry rare genetic variants in the CFH gene that cause functional or quantitative deficiencies in the factor H (FH) protein, an important regulator of the AP. In silico analysis of the deleteriousness of rare genetic variants in CFH is not reliable and careful biochemical assessment remains the gold standard. Six N-terminal variants of uncertain significance in CFH were identified in patients with these diseases of the AP and selected for analysis. The variants were produced in Pichia Pastoris in the setting of FH CCPs 1–4, purified by nickel affinity chromatography and size exclusion and characterized by surface plasmon resonance and haemolytic assays as well as by cofactor assays in the fluid phase. A single variant, Q81P demonstrated a profound loss of binding to C3b with consequent loss of cofactor and decay accelerating activity. A further 2 variants, G69E and D130N, demonstrated only subtle defects which could conceivably over time lead to disease progression of more chronic AP diseases such as C3G and AMD. In the variants S159N, A161S, and M162V any functional defect was below the capacity of the experimental assays to reliably detect. This study further underlines the importance of careful biochemical assessment when assigning functional consequences to rare genetic variants that may alter clinical decisions for patients.